Alternative Energy Sources Usable in Automotive Transport - Jiří Zukal; Zoltán Szabó; Miloš Klíma; Pavel Fiala (Inventions)
The research focuses on the methodology of preparing a concept and application scenarios for alternative sources of energy in transportation. The ideas and interpretations are not strictly limited to automobile transport but also reach into other areas of using and processing energy. The conceptual approach to the choice of sources, with the aim of securing the efficient use of energy conversion, is illustrated on the model embodiment embedded in a passenger car; the relevant presentation is centered on an experiment focusing on the linear arrangement of a driven electromagnetic generator. This involves generating and collecting energy for not only the accumulation of electrical energy using relatively independent systems, but also for direct use within driving needs. In the modeled example, the supplied energy is assumed to be in a range of constant power from p = 10 W to 50 kW (200 kW). The given example of the design of the choice of energy conversion sources and the use of generators in a passenger car shows the possibilities, limitations, and variants for demonstrating the requirements relating to a simple driving mode. The application of a linear or cylindrical internal combustion engine is considered for a specific set mode of the car. Variants of suitable uses of the accumulated energy in compressed air are proposed. The use of light and thermal forms of energy is considered for additional forms. As an experimental example, the use of generators derived from vibration harvesters is shown. The proposed energy generation arrangement can be controlled and optimized for specific transport tasks. The generation and accumulation of energy can be employed in the form of electrical energy, as kinetic energy for direct use in driving, or to accumulate in compressed air for later use. Solar energy can be used directly or can be accumulated. The combustion unit can serve as a source of kinetic energy or also to store energy for further use. The concept of alternative sources is based on known methods of use in other industries. The model combination of resources and its simple analysis in the concept of resource selection is demonstrated on an example of an application in passenger cars.